The Cyber Security Handbook - Prepare for, Respond to and Recover from Cyber Attacks - Calder, Alan (IT Governance Ltd, 2020)
This book is a comprehensive cyber security implementation manual which gives practical guidance on the individual activities identified in the IT Governance Cyber Resilience Framework (CRF) that can help organisations become cyber resilient and combat the cyber threat landscape. Start your cyber security journey and buy this book today!